2018
DOI: 10.1002/jum.14694
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Long‐, Short‐, and Oblique‐Axis Approaches for Ultrasound‐Guided Vascular Access Cannulation

Abstract: There was insufficient evidence to definitively recommend the LAX, SAX, or OAX approach for patients undergoing ultrasound-guided vascular access cannulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 24 publications
(35 reference statements)
0
18
0
Order By: Relevance
“…Ultrasound-guided vein intervention methods have been compared and studied multiple times in the past [9,10]. There are studies that determined that long axis, short axis, and oblique axis approaches while applying an ultrasound-guided internal jugular venous catheterization don't provide different results within the context of success [11]. Even though it is reported that the primary intervention process takes a shorter period in short axis out of plane approach when compared to the long axis, this difference is not determined as significant [12].…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound-guided vein intervention methods have been compared and studied multiple times in the past [9,10]. There are studies that determined that long axis, short axis, and oblique axis approaches while applying an ultrasound-guided internal jugular venous catheterization don't provide different results within the context of success [11]. Even though it is reported that the primary intervention process takes a shorter period in short axis out of plane approach when compared to the long axis, this difference is not determined as significant [12].…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous studies and reviews published describing and comparing the various US and traditional landmark techniques. [6][7][8][9][10][11] Shortcomings of the various techniques are discussed, and alternatives and alterations presented. [12][13][14][15] With few exceptions, USguided IJV access has been associated with a higher success rate on first attempt, fewer failed attempts, and higher success rate overall, and frequently was associated with fewer complications.…”
Section: Editorialmentioning
confidence: 99%
“…While the benefit of ultrasound-guided cannulation is well established 7,8 studies assessing the effect of its orientation on cannulation of the larger calibre internal jugular vein (IJV) are inconsistent. [9][10][11] This heterogeneity limits generalisability to the smaller, less accessible lower limb venous trunks. At present, despite its widespread application, there is a paucity of evidence to guide ultrasound orientation during access for lower limb endovenous ablation.…”
Section: Introductionmentioning
confidence: 99%